DOES (FAMILY) LAW PROTECT FAMILY? - Kovaček Stanić, Gordana; Samardžić, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Although we cannot ignore the fact that the law in some way affects the family from the very beginning by determining who is considered a family member, what are their mutual rights and obligations, how certain relationships are formed and how they end, modern understanding of the family, however, necessarily implies respect for the extremely wide field of family, that is parental autonomy. Such an understanding could, in the most extreme form, result in an almost complete absence of responsibility of the state or the legal system for everything that happens in the family. In this sense, there are very weak formal legal obligations of the state in taking an active role in strengthening the family, and in practice there is virtually no involvement of the state in strengthening ties within the family before certain problems arise. On the other hand, if someone has the potential to protect the family and its members, then it is certainly the legal system. The protection of the family must not be reduced only to the question of how to do it, but also at what moment or whether the protection and development of healthy family relationships must be an issue to be addressed much earlier, even before the family is formed. In that sense, counseling or conversations with competent persons, can be of special importance. Also, although they are relatively foreign to our culture, the popularization of prenuptial agreements and presenting future spouses or common law partners with the possibilities of this agreement provides, can contribute to the avoidance of later property disputes. In this paper, the focus will, however, be on certain solutions that can help in situations where there is already a disturbance in the relationship between family members, that is between spouses or common law partners. Any attempt to calm the situation, or  moderate and careful intervention in family relations, can primarily be achieved by insisting on certain alternative ways of resolving disputes. In addition, the existence of specialized judges, as well as lawyers, who would implement significant changes in the education system of future lawyers, but also in the field of practice, can also greatly contribute to this goal. Finally, certain changes in the field of family substantive law can also be of great importance. In that sense, this paper primarily focuses on certain solutions proposed in theory, their analysis in the context of Serbian legislation, as well as on possible further changes in domestic regulations. Namely, although some proposals have already found their place in the positive legislation of Serbia, it remains uncertain to what extent these provisions have been applied and whether they really contribute to maintaining stable family relations in situations when relations are seriously disturbed.
Keywords: family law, mediation, exercising parental responsibility, family disputes